Modulation of primary cell function of host Pseudomonas bacteria by the conjugative plasmid pCAR1. (24th June 2014) - Takahashi, Yurika; Shintani, Masaki; Takase, Noriyuki; Kazo, Yuka; Kawamura, Fujio; Hara, Hirofumi; Nishida, Hiromi; Okada, Kazunori; Yamane, Hisakazu; Nojiri, Hideaki
Summary The impacts of plasmid carriage on the host cell were comprehensively analysed using the conjugative plasmid pCAR1 in three different Pseudomonas hosts, P. putida KT2440, P. aeruginosa PAO1 and P. fluorescens Pf0‐1. Plasmid carriage reduced host fitness, swimming motility, and resistance to osmotic or pH stress. Plasmid carriage brought about alterations in primary metabolic capacities in the TCA cycle of the hosts. Differentially transcribed genes in the three hosts associated with plasmid carriage were identified by growth phase‐dependent transcriptome analyses. Plasmid carriage commonly showed a greater effect on the host transcriptome at the transition and early stationary phases. The transcriptome alterations were similar between KT2440 and PAO1. Transcriptions of numbers of genes encoding ribosomal proteins, F‐type ATPase, and RNAP core in both strains were not suppressed enough in the early stationary phase by plasmid carriage. These responses may have been responsible for the reduction in host fitness, motility and stress resistances. Host‐specific responses to plasmid carriage were transcriptional changes of genes on putative prophage or foreign DNA regions. The extents of the impacts on host phenotypes and transcriptomes were similarly greatest in KT2440 and lowest in Pf0‐1. These findings suggest that host cell function was actively regulated by plasmid carriage.